Using concept maps to improve English reading comprehension ability: A case study of Prathom Suksa 5 students with low English proficiency - สุวรรณ โสพินญา; เลาหวิริยานนท์ ชลลดา (Journal of Liberal Arts Prince of Songkla University, 2016)
The objectives of this case study were to investigate the effects of the use of concept maps on low proficiency students’ reading comprehension ability and to investigate their ability to independently create the concept maps. Out of twenty-two Prathom Suksa 5 students, the subjects of this study consisted of only eight students who had low English proficiency. They were studying at Ban Klong Wa (Taweerat Radbamrung) primary school situated in Hat Yai District, Songkhla. The experiment took place in the first semester of the academic year 2011. Quantitative data were obtained from the results of the multiple-choice pre-and post-tests. Qualitative data were taken from the results of the pre- and post-written-recall protocols and four interview sessions conducted after the completion of each teaching unit. The quantitative results demonstrated the significant increase of the post test scores at the level of .01 with large effect size (1.72). As for the three reading sub-skills, it was found that reading for gist was the sub-skill on which the subjects obtained the highest score, followed by drawing inferences, and reading for specific details respectively. The qualitative results, however, revealed that despite having a positive attitude towards the use of concept maps, the subjects still could not create concept maps individually. They needed considerable guidance from the teacher due to their limited English vocabulary. It is recommended that future studies employ various types of concept maps suitable for various text types with students studying at higher educational levels.